TECHNOLOGICAL APPROACH IN THE DESIGN OF INDEPENDENT EDUCATION ON THE SUBJECT “INFORMATION TECHNOLOGY IN EDUCATION” - Ismatovna, Asadova Yulduz (PT ANTIS International Publisher, 2024)
This article discusses theoretical aspects of teaching in an e-learning environment, in accordance with information technology science programs in education. It also provides a methodology for using electronic platforms to help students manage independent study hours allocated for subjects in a modular credit system at higher education institutions. In addition, students can use these platforms during educational training sessions to master independent learning topics. From this article, students can gain advice and answers to questions they may have, which can be used to organize independent learning in all types of higher education institutions